Optimization of Foreign Market Entry Through Adaptation to Changing Market Trends in The Destination Country - Siswati, Endang; Rapitasari, Diana (Publisher Cv. Inara, 2024)
This research is qualitative research at Artistica Jewelry which aims to determine the optimization of foreign markets through adapting to changing trends, to determine the challenges faced by companies in adapting to changing trends. How new growth opportunities emerge in foreign markets as a result of the adaptations faced by the company. This research analyzes secondary data, including company reports and related literature. Data collection techniques use interview, observation and documentation techniques. The research results reveal that Artistica Jewelry Surabaya has succeeded in expanding its market share in the target country market by adapting to consumer desires, innovating in product design. The challenges faced by companies in adapting include: consumer tastes changing rapidly, aspects of technology and innovation, the rapid development of e-commerce, competitive competition, as well as aspects of sustainability and ethics in business which are currently intensely discussed by people. Opportunities that arise as a result of adaptation are being able to gain a competitive advantage in increasingly complex international markets. This provides useful insights for other companies looking to strengthen their presence in foreign markets.